60 Association of systemic lupus erythematosus (SLE) genetic susceptibility loci with lupus nephritis in childhood-onset and adult-onset with SLE. (April 2019) - Webber, Declan; Cao, Jingjing; Dominguez, Daniela; Gladman, Dafna D; Levy, Deborah; Ng, Lawrence; Paterson, Andrew; Touma, Zahi; Urowitz, Murray B; Wither, Joan; Silverman, Earl D; Hiraki, Linda T
Abstract : Background: Lupus nephritis (LN) is one of the most common and severe manifestations of systemic lupus erythematosus (SLE). We tested the association of SLE-risk loci with LN risk in childhood- (cSLE) and adult-onset SLE (aSLE). Methods: Two Toronto-based tertiary care SLE cohorts included cSLE (diagnosed <18 y) and aSLE patients (diagnosed 18y). Patients met ACR and/or SLICC SLE criteria and were genotyped on the Illumina MEGA or Omni1 arrays. Ungenotyped SNPs were imputed (1000 Genomes Project). HLA alleles were imputed in the Europeans only (SNP2HLA). Ancestry was inferred using principal components. We identified those with and without biopsy confirmed LN. HLA and non-HLA additive SLE risk-weighted genetic risk scores (GRSs) were tested for association with LN risk in logistic models, stratified by cSLE/aSLE and ancestry. Stratified effect estimates were meta-analyzed. Results: Of 1237 participants, 572 had cSLE (41% with LN) and 665 had aSLE (30% with LN). Increasing non-HLA GRS was significantly associated with increased LN risk (OR=1.26; 95% CI: 1.09, 1.46, p=0.0006) as was increasing HLA GRS in Europeans (OR=1.55; 95% CI: 1.07, 2.25; p=0.03). There was a trend for stronger associations between both GRSs and LN risk in Europeans with cSLE compared with aSLE. Conclusions: We observed an association between known SLE-risk loci and LN risk in children and adults with SLE, with the strongest effect observed among Europeans with cSLE. Future directions will include incorporating SLE-risk SNPs specific to non-European ancestral groups and validating findings in an independent cohort. Funding Source(s): Dr. Hiraki: Canadian Institute of Health Research (CIHR) Project Scheme grant